2019
DOI: 10.1021/acs.jafc.9b05473
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Arabidopsis Blue Light Receptor LOV Domain Variants with Improved Quantum Yield, Brightness, and Thermostability

Abstract: Despite remarkable contribution of green fluorescent protein and its variants for better understanding of various biological functions, its application for anaerobic microorganisms has been limited because molecular oxygen is essential for chromophore formation. To overcome the limitation, we engineered a plant-derived light, oxygen, or voltage (LOV) domain containing flavin mononucleotide for enhanced spectral properties. The resulting LOV variants exhibited improved fluorescence intensity (20 and 70% higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Previous efforts to improve the usability of iLOV resulted in the generation of phiLOV, an iLOV derivative which possesses a superior photostability, thus tackling one of the major drawbacks in using iLOV 23 . Very recently improved brightness of iLOV variants have been reported 13,14 . It remains to be seen whether the introduced mutations responsible for the increased photostability and brightness of new iLOV variants can be applied to improve the visualization of iLOV V392K , without interfering with its excitation and emission spectra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous efforts to improve the usability of iLOV resulted in the generation of phiLOV, an iLOV derivative which possesses a superior photostability, thus tackling one of the major drawbacks in using iLOV 23 . Very recently improved brightness of iLOV variants have been reported 13,14 . It remains to be seen whether the introduced mutations responsible for the increased photostability and brightness of new iLOV variants can be applied to improve the visualization of iLOV V392K , without interfering with its excitation and emission spectra.…”
Section: Discussionmentioning
confidence: 99%
“…So far, all experimentally obtained FbFPs share spectral features similar to GFP 12 . However, FbFPs possessed relatively weak fluorescent intensity until very recently 13,14 . Engineering a red-shifted FbFP could address this problem by shifting the excitation and emission peaks away from the cellular autofluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies focused on the effects of mutating the conserved cysteine, which forms a covalent bond with the flavonoid cofactor during the photocycle, and some random mutations on flavin binding and photochemical reactivity [55,56]. Later studies probed the effects of mutations on other properties, particularly the absorption spectrum [47,50,57,58], photocycle lifetime [57,59], brightness of the cysteine-less variants [9,19,20,60], generation of radicals [15,61,62] and thermal stability [21][22][23]. Many of these mutations were rational, or could be rationalized after initial discovery, thus allowing one to apply the same principles to impart a different LOV domain with the desirable properties.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the effects of the proline substitutions may also be transferable to other LOV domains, since the rationales that we employed (consensus design [26][27][28], stabilization by prolines [27,28]) will hold. Interestingly, out of three LOV domain thermal stabilization studies [21][22][23], only one reported the proline substitutions [22], which were, however, not included in the most stable variant with multiple mutations. Thus, testing the effects of proline substitutions may be a complementary approach to recombination, and directed evolution to speed up the discovery of the most stable variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation